2021
DOI: 10.1016/j.ultsonch.2021.105630
|View full text |Cite
|
Sign up to set email alerts
|

Continuous and pulsed ultrasound-assisted extraction of carob’s antioxidants: Processing parameters optimization and identification of polyphenolic composition

Abstract: Highlights CUAE and PUAE parameters were optimized by the maximization of the yield in TPC. Compared to conventional methods, UAE offered a higher yield of antioxidants. Gallic acid was the most abundant polyphenolic compound in carob pulp extracts. Solvent concentration was the most influential processing parameter. DPA-6S demonstrated the best ability to recuperate the target analytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 50 publications
5
36
3
2
Order By: Relevance
“…It means that an increase or decrease of polyphenols concentration was observed when X 3 and X 4 were changed from lower to higher level. This behavior was similarly reported in a recent study dealing with ultrasound extractions from carob pods, in which solvent concentration and solid to solvent ratio were among the three most dominant factors that influenced the polyphenols recovery, while, conversely to our finding, the other determinant factor was the sonication power [17]. Probably, this difference could be ascribed to the use by Christou et al [17] of an ultrasonic probe system in their experiment; indeed, a previous research have demonstrated that, when an ultrasonic water bath is employed for extracting D-pinitol from carob pods, the sonication power is not statistically significant [19].…”
Section: Screening Of Factors Influencing Uae Efficiencysupporting
confidence: 92%
See 2 more Smart Citations
“…It means that an increase or decrease of polyphenols concentration was observed when X 3 and X 4 were changed from lower to higher level. This behavior was similarly reported in a recent study dealing with ultrasound extractions from carob pods, in which solvent concentration and solid to solvent ratio were among the three most dominant factors that influenced the polyphenols recovery, while, conversely to our finding, the other determinant factor was the sonication power [17]. Probably, this difference could be ascribed to the use by Christou et al [17] of an ultrasonic probe system in their experiment; indeed, a previous research have demonstrated that, when an ultrasonic water bath is employed for extracting D-pinitol from carob pods, the sonication power is not statistically significant [19].…”
Section: Screening Of Factors Influencing Uae Efficiencysupporting
confidence: 92%
“…Among them, ultrasound assisted extraction 2 of 13 (UAE) is engaging for its simplicity and low cost of equipment [14,15]; it is much quicker than conventional methods, because acoustic cavitations of power US (preferably in the frequencies range 18-100 kHz) cause cell walls disruption, increasing mass transfer and favoring solvent access to the cell content [16]. The efficiency of UAE is generally influenced by several factors, including solvent-solid ratio, solvent type and concentration, particle size, and extraction time and temperature [17]. Many researches have shown that the highest extraction of polyphenols and other bioactive compounds was obtained with ultrasound technology and the application of suitable optimization modelling was essential to identify the optimized extraction conditions [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental Designs 2.6.1. Full Factorial Design Experiments Full factorial design (FFD) experiments designed by Design Expert 10.0.0 software (Sta-Ease, Minneapolis, MN, USA) were conducted for initial screening of key UAE parameters [13,26]. A five-factor two-level FFD experimental was carried out to investigate the influences of water content in DES (A), liquid to solid ratio (B), extraction time (C), ultrasonication power (D), and ultrasonication temperature (E) on TPC and TFC (Table S1).…”
Section: α-Glucosidase Inhibitory Activity (α-Gia) Assaymentioning
confidence: 99%
“…There was no significant difference between continuous and pulsing irradiation despite the great difference in energy consumption (190 kJ vs. 80 kJ). On the other hand, Christou et al [36] during polyphenol recovery from mature and immature carobs, achieved a slightly higher efficiency when UAE was performed in the pulsed mode. The ultrasonic processor runs intermittently during pulse ultrasound assisted extraction (PUAE).…”
Section: Introductionmentioning
confidence: 97%